Using a list experiment to measure intimate partner violence: Cautionary evidence from Ethiopia - Gilligan, Daniel O.; Hidrobo, Melissa; Leight, Jessica; Tambet, Heleene (Informa UK Limited, 2025)
While indirect response methods are increasingly used in surveys to measure sensitive behaviours such as intimate partner violence, important questions persist around how respondents understand and react to these methods. This article presents evidence from a list experiment measuring multiple forms of intimate partner violence in rural Ethiopia. We find that the list experiment does not generate estimates of intimate partner violence that are higher than direct response questions; rather, prevalence estimates using the list experiment are lower vis-à-vis prevalence estimates using the direct reports, and are sometimes even negative. We provide suggestive evidence that this pattern may reflect ‘fleeing’ behaviour by respondents who do not wish to be associated with statements indicating their exposure to intimate partner violence.